PESSOA ON CAMÕES’ OS LUSÍADAS: METER, GRAMMAR AND RHYTHM - Arias Navarro, Javier; Ferrari, Patricio (Rhythmica. Revista Española de Métrica Comparada, 2015)
The present paper focuses on the philological reconstruction and account of Fernando Pessoa’s scansion of one verse from Os Lusíadas, as presented in some unpublished draft notes for his projected Treaty of Prosody and Poetics. To begin with, Pessoa’s analysis of rhythmic pauses is introduced. Secondly, Robert Bridges’ «stressunits » are presented, which constituted the main inspiration for Pessoa’s scansion. Furthermore, a brief interpretation in terms of the generative theory of meter is put forward, which underscores the analogies and differences between the two linguistic traditions Pessoa worked with. Last but not least, the implications of Pessoa’s scansion for phrasing in Camões’ verse are also taken into account. A critical transcription of Pessoa’ s analysis on Camões is included in the Annex.